Sodium ion negative electrode-free battery, current collector and preparation method thereof
By loading iron phosphide and porous carbon composites on the nickel foam matrix of sodium-ion negative-electrode batteries, the problems of low battery energy density and poor conductivity are solved, high specific surface area and conductivity of the current collector are achieved, and sodium dendrites are suppressed. crystal growth.
Patent Information
- Application Number
- CN202411377087.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-30
AI Technical Summary
Sodium ion negative electrode-free batteries have problems with low energy density and poor conductivity.
A nickel foam matrix is used and a composite loaded on its surface and pore walls is used. The composite is composed of iron phosphide and porous carbon, and a sodium ion negative-electrode battery current collector is formed through a specific preparation method.
It improves the specific surface area and conductivity of the current collector, provides abundant sodium ion deposition sites, and can effectively inhibit the growth of sodium dendrites.
Smart Images

Figure CN118899449B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of battery materials, and in particular to a sodium ion negative electrode-free battery, a current collector and a preparation method thereof. Background Art
[0002] The negative electrode-free sodium metal battery is a battery that stores and releases energy based on sodium ions. Unlike traditional sodium ion batteries, sodium can form a metallic state on the current collector to minimize the loss of electron flow. At the same time, the positive electrode material stores and releases energy by adsorbing and releasing sodium ions. This design effectively solves the capacity limitation and charge transfer speed bottleneck problems of traditional battery negative electrode active materials (such as hard carbon), and also has the advantages of good low temperature performance, low cost, high safety and long cycle life. Although the negative electrode-free sodium metal battery has the above advantages, it still has serious problems such as low energy density and poor conductivity.
[0003] In view of this, the present invention is proposed. Summary of the invention
[0004] The object of the present invention is to provide a sodium ion negative electrode-free battery, a current collector and a preparation method thereof.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a sodium ion negative electrode-free battery current collector, comprising a foamed nickel substrate and a composite supported on the surface of the foamed nickel substrate and the pore walls of the pores;
[0007] The components of the composite include iron phosphide and porous carbon;
[0008] The mass ratio of porous carbon to iron phosphide is 1 to 1.5:1;
[0009] The mass ratio of the composite to the nickel foam matrix is 4~5:5.
[0010] In a second aspect, the present invention provides a method for preparing a sodium ion negative electrode-free battery current collector according to the aforementioned embodiment, comprising:
[0011] Oxidizing the nickel foam to form a nickel oxide layer on the surface of the nickel foam to obtain an oxidized nickel foam;
[0012] The oxidized nickel foam and the acid solution of ferrocyanide are mixed and reacted to make the nickel oxide on the surface of the oxidized nickel foam react with the ferrocyanide to generate nickel ferrocyanide, thereby obtaining nickel foam-loaded nickel ferrocyanide;
[0013] The nickel foam loaded with nickel ferrocyanide is calcined at 600-800°C to convert the nitrogen in the cyanide into nitrogen gas overflow, the carbon in the cyanide into elemental carbon particles, and the iron into elemental iron, thereby obtaining a nickel-iron-carbon precursor;
[0014] The nickel-iron-carbon precursor is calcined at 600-800°C for 10-40 minutes in a carbon dioxide atmosphere, so that the carbon dioxide partially reacts with the elemental carbon particles to generate carbon monoxide, and a porous structure is formed on the carbon particles, thereby converting the elemental carbon particles into porous carbon, and obtaining an iron-nickel porous carbon precursor;
[0015] In a closed environment, the iron-nickel porous carbon precursor is fully reacted with phosphine gas at 350-450°C to make iron and phosphorus react to form iron phosphide, thereby obtaining a sodium ion negative electrode-free battery current collector.
[0016] In an optional embodiment, before the nickel foam is oxidized, the surface of the nickel foam is treated to remove the original uneven oxide layer on the surface of the nickel foam;
[0017] The method of removing the original uneven oxide layer on the surface of the nickel foam includes: washing the nickel foam with acetone and water in turn, and then placing it in an acid solution for reaction.
[0018] In an optional embodiment, the invention comprises at least one of the following technical features (1) and (2):
[0019] (1) The acid solution is selected from at least one of dilute sulfuric acid, dilute hydrochloric acid, citric acid and tartaric acid;
[0020] (2) The molar concentration of the acid solution is 0.5~1 mol / L, and the reaction time is 1~6h.
[0021] In an optional embodiment, the method comprises at least one of the following features (1) to (11);
[0022] (1) The pH of the acid solution of ferrocyanide is 2 to 5;
[0023] (2) the ferrocyanide is at least one selected from the group consisting of potassium ferrocyanide, potassium ferrocyanide and sodium ferrocyanide;
[0024] (3) The mixed reaction of the nickel oxide foam and the acid solution of ferrocyanide is carried out in a sealed container;
[0025] (4) The molar concentration of ferrocyanide in the acid solution of ferrocyanide is 0.1~0.7 mol / L;
[0026] (5) The mass ratio of the acid solution of ferrocyanide to the nickel oxide foam is 20-100:5;
[0027] (6) The acid solution of ferrocyanide is a mixture of ferrocyanide and dilute acid, wherein the dilute acid is dilute sulfuric acid or dilute hydrochloric acid;
[0028] (7) The method of oxidizing the nickel foam includes: placing the nickel foam in an oxygen environment at 100-140° C. for oxidation treatment for 0.5-1.5 hours;
[0029] (8) The reaction time of mixing the nickel oxide foam and the acid solution of ferrocyanide is 0.5 to 2 hours;
[0030] (9) When the nickel foam loaded with nickel ferrocyanide is calcined, it is carried out in an argon atmosphere or a mixed atmosphere of argon and hydrogen;
[0031] (10) When the nickel foam loaded with nickel ferrocyanide is calcined, the calcination time is 5 to 7 hours;
[0032] (11) After the nickel-iron-carbon precursor is calcined in a carbon dioxide atmosphere, annealing is also performed for 50 to 70 minutes.
[0033] In an optional embodiment, the method of fully reacting the iron-nickel porous carbon precursor with phosphine gas at 350-450° C. in a closed environment includes:
[0034] In a closed environment with an inert atmosphere, sodium hypophosphite is decomposed into phosphine gas which fills the closed environment. The temperature of the closed environment is controlled at 350-450°C and the reaction is carried out for 5-7 hours.
[0035] In an optional embodiment, the mass ratio of the amount of sodium hypophosphite to the nickel foam is 1-0.8:5.
[0036] In an optional embodiment, the method further includes at least one of the following features (1) to (3):
[0037] (1) Control the temperature of the sealed environment to 350-450°C, react for 5-7 hours and then anneal for 50-70 minutes;
[0038] (2) The inert atmosphere is argon atmosphere;
[0039] (3) The method of decomposing sodium hypophosphite into phosphine includes: placing the sodium hypophosphite in a closed environment with an inert atmosphere, raising the ambient temperature to 180-220°C, and maintaining it for 1.5-2.5 hours to allow the sodium hypophosphite to completely decompose.
[0040] In a third aspect, the present invention provides a sodium ion negative electrode-free battery, comprising a current collector as in any one of the aforementioned embodiments or a current collector prepared by the preparation method as in any one of the aforementioned embodiments.
[0041] The present invention has the following beneficial effects:
[0042] The sodium ion negative electrode-free battery current collector provided by the present invention has an excellent three-dimensional structure, and the combination of the nickel foam and the porous carbon loaded on the surface and the pore wall of the pore structure can give the current collector an ultra-high specific surface area; the porous carbon has a rich pore structure, which can provide abundant sites for the deposition of sodium ions; and the iron phosphide can increase the conductivity of the composite. Therefore, the sodium ion negative electrode-free battery current collector provided by the present invention has abundant sodium ion deposition sites and excellent conductivity, so it has the effect of inhibiting the growth of sodium dendrites. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0044] Figure 1 This is a SEM image of the current collector prepared in Example 1 at the first magnification;
[0045] Figure 2 This is a SEM image of the current collector prepared in Example 1 at the second magnification. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0047] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0048] The sodium ion negative electrode-free battery, current collector and preparation method thereof provided in the embodiments of the present invention are described in detail below.
[0049] A sodium ion negative electrode-free battery current collector provided in an embodiment of the present invention comprises a nickel foam substrate and a composite material supported on the surface of the nickel foam substrate and the pore walls of the pores;
[0050] The components of the composite include iron phosphide and porous carbon;
[0051] The mass ratio of porous carbon to iron phosphide is 1 to 1.5:1 (e.g., 1:1, 1.2:1 or 1.5:1);
[0052] The mass ratio of the composite to the nickel foam matrix is 4 to 5:5 (eg, 4:5, 4.5:5 or 5:5).
[0053] Nickel foam has an excellent three-dimensional structure, and the porous carbon loaded on its surface and the pore wall of the pore structure can give the current collector an ultra-high specific surface area; the porous carbon has a rich pore structure, which can provide abundant sites for the deposition of sodium ions; and iron phosphide can increase the conductivity of the current collector. Therefore, the sodium ion negative electrode-free battery current collector provided by the embodiment of the present invention has abundant sodium ion deposition sites and excellent conductivity, so it has the effect of inhibiting the growth of sodium dendrites.
[0054] The method for preparing the sodium ion negative electrode-free battery current collector provided in an embodiment of the present invention comprises:
[0055] Oxidizing the nickel foam to form a nickel oxide layer on the surface of the nickel foam to obtain an oxidized nickel foam;
[0056] The oxidized nickel foam and the acid solution of ferrocyanide are mixed and reacted to make the nickel oxide on the surface of the oxidized nickel foam react with the ferrocyanide to generate nickel ferrocyanide, thereby obtaining nickel foam-loaded nickel ferrocyanide;
[0057] The nickel foam loaded nickel ferrocyanide is placed in an environment of 600-800°C (e.g., 600°C, 700°C, or 800°C) and calcined to convert the nitrogen element in the cyanide into nitrogen gas overflow, the carbon in the cyanide into elemental carbon particles, and the iron element into elemental iron, thereby obtaining a nickel-iron-carbon precursor;
[0058] The nickel-iron-carbon precursor is calcined at 600-800° C. (e.g., 600° C., 700° C., or 800° C.) in a carbon dioxide atmosphere for 10-40 min (e.g., 10 min, 20 min, 30 min, or 40 min), so that the carbon dioxide partially reacts with the elemental carbon particles to generate carbon monoxide, and a porous structure is formed on the carbon particles, thereby converting the elemental carbon particles into porous carbon, thereby obtaining an iron-nickel porous carbon precursor;
[0059] In a closed environment, the iron-nickel porous carbon precursor is fully reacted with phosphine gas at 350-450°C (eg, 350°C, 400°C or 450°C) to allow iron and phosphorus to react into iron phosphide, thereby obtaining a sodium ion negative electrode-free battery current collector.
[0060] Through the preparation method provided in the embodiment of the present invention, the sodium ion negative electrode-free battery current collector provided in the embodiment of the present invention, which has excellent conductivity and can inhibit the growth of sodium dendrites, can be obtained.
[0061] The preparation method is specifically as follows:
[0062] S1. Nickel foam pretreatment
[0063] Remove the original uneven oxide layer on the surface of nickel foam. The specific method is:
[0064] The nickel foam is washed with acetone and water successively, and then placed in an acid solution for reaction. After the reaction is completed, it is washed with deionized water for several times to obtain clean nickel foam.
[0065] Preferably, in order to fully remove the oxide layer on the surface of the nickel foam, the acid solution is selected from at least one of dilute sulfuric acid, dilute hydrochloric acid, citric acid and tartaric acid.
[0066] Preferably, the molar concentration of the acid solution is 0.5-1 mol / L (eg, 0.5 mol / L, 0.8 mol / L or 1 mol / L), and the reaction time is 1-6 h (eg, 1 h, 2 h, 4 h or 6 h).
[0067] The embodiment of the present invention uses commercial nickel foam as a raw material, which is cheap.
[0068] After the nickel foam surface is pretreated, there are no impurities and oxides on its surface, which can ensure that a uniform and dense nickel oxide layer is formed on the nickel foam surface during the subsequent pre-oxidation process, thereby ensuring that a positive electrode material with good electrochemical performance is obtained.
[0069] S2, Nickel Oxide Foam
[0070] The clean nickel foam is oxidized to form a uniform and dense nickel oxide layer on the surface of the nickel foam to obtain oxidized nickel foam.
[0071] Specifically, the method of oxidizing the nickel foam includes:
[0072] The nickel foam is placed in an oxygen environment at 100-140° C. (eg, 100° C., 120° C., or 140° C.) and oxidized for 0.5-1.5 h (eg, 0.5 h, 1 h, or 1.5 h).
[0073] S3. Preparation of nickel foam loaded with nickel ferrocyanide
[0074] The oxidized nickel foam and the acid solution of ferrocyanide are mixed and reacted, so that the nickel oxide on the surface of the oxidized nickel foam reacts with the ferrocyanide to generate nickel ferrocyanide, thereby obtaining the nickel foam-loaded nickel ferrocyanide.
[0075] The specific steps of this step are:
[0076] Weigh a certain amount of ferrocyanide and dissolve it in water, and use dilute acid to adjust the pH value to 3-4 to obtain an acid solution of ferrocyanide, which is then sealed for later use.
[0077] The oxidized nickel foam obtained in step S2 is placed in a sealed container of an acid solution of ferrocyanide and allowed to stand for about 1 hour, so that the surface of the nickel foam is evenly complexed with nickel ferrocyanide.
[0078] Optionally, the dilute acid is selected from at least one of dilute sulfuric acid and dilute hydrochloric acid.
[0079] Optionally, the molar concentration of ferrocyanide in the acid solution of ferrocyanide is 0.1-0.7 mol / L (e.g., 0.1 mol / L, 0.2 mol / L, 0.5 mol / L or 0.7 mol / L), preferably 0.25-0.5 mol / L (e.g., 0.25 mol / L, 0.3 mol / L or 0.5 mol / L).
[0080] Optionally, the dosage of the ferricyanide acid solution and the oxidized nickel foam is such that the oxidized nickel foam can be completely immersed in the ferricyanide acid solution.
[0081] Optionally, the ferrocyanide is selected from at least one of potassium ferrocyanide, potassium ferrocyanide and sodium ferrocyanide.
[0082] Optionally, the nickel oxide foam and the acid solution of ferrocyanide are mixed and reacted for 0.5 to 2 h (eg, 0.5 h, 1 h, 1.5 h or 2 h) so that the nickel oxide and ferrocyanide fully react to form nickel ferrocyanide.
[0083] S4, first calcination
[0084] The nickel foam loaded nickel ferrocyanide is placed in a tubular furnace at 600-800°C (e.g., 600°C, 700°C or 800°C) and calcined to break the C-Fe bond, convert the nitrogen element in the cyanide into nitrogen gas overflow, convert the carbon in the cyanide into elemental carbon particles, and convert the iron element into elemental iron, thereby obtaining a nickel-iron-carbon precursor.
[0085] Optionally, the calcination step is performed in an argon atmosphere or a mixed atmosphere of argon and hydrogen. Preferably, in order to fully convert the iron element into elemental carbon, the calcination atmosphere is a mixed atmosphere of argon and hydrogen.
[0086] Optionally, the calcination time is 5 to 7 hours (eg, 5 hours, 6 hours or 7 hours), so that the nitrogen element is converted into nitrogen gas overflow, the carbon element is converted into elemental carbon particles, and the iron element is converted into elemental iron.
[0087] S5. Second calcination
[0088] The nickel-iron-carbon precursor is calcined at 600-800°C (e.g., 600°C, 700°C, or 800°C) for 10-40 minutes (e.g., 10 minutes, 20 minutes, 30 minutes, or 40 minutes) in a carbon dioxide atmosphere. Carbon dioxide reacts partially with elemental carbon particles to generate carbon monoxide, forming a nanoscale pore structure on the carbon particles, thereby converting the elemental carbon particles into porous carbon to obtain an iron-nickel porous carbon precursor.
[0089] It should be noted that the calcination temperature and time need to be controlled within the above range. If the temperature is too high, the carbon particles will be consumed faster and the calcination time will be difficult to control. If the reaction time is too long, the carbon particles will react completely and no porous carbon will be generated.
[0090] In order to improve the toughness of the porous carbon layer, annealing is further performed for 50 to 70 minutes (eg, 50 minutes, 55 minutes, 60 minutes or 70 minutes) after the calcination.
[0091] S6. Phosphating reaction
[0092] In a closed environment, the iron-nickel porous carbon precursor is fully reacted with phosphine gas at 350-450°C (eg, 350°C, 400°C or 450°C) to allow iron and phosphorus to react into iron phosphide, thereby obtaining a sodium ion negative electrode-free battery current collector.
[0093] Specifically, a certain amount of sodium hypophosphite is placed in the middle section of a tubular furnace quartz tube, and an iron-nickel porous carbon precursor is placed directly above the sodium hypophosphite. In an inert atmosphere (argon), the ambient temperature is raised to 180-220°C (e.g., 180°C, 200°C, or 220°C) and pre-calcined for 1.5-2.5h (e.g., 1.5h, 2h, or 2.5h) to fully decompose the sodium hypophosphite into phosphine gas, and then the temperature is raised to 350°C-450°C (e.g., 350°C, 400°C, or 450°C) and calcined for 5-7h (e.g., 5h, 6h, or 7h). Afterwards, annealing is performed in an atmosphere still containing argon for 50-70min (e.g., 50min, 55min, 60min, or 70min) to obtain a sodium ion negative electrode-free battery current collector.
[0094] Optionally, in this step, the tubular furnace is filled with inert gas and then closed to create a closed space, and then the temperature is raised for pre-calcination, so that the concentration of phosphine gas can be kept at a maximum and stable, making the phosphating more complete and uniform.
[0095] The sodium ion negative electrode-free battery provided in the embodiment of the present invention comprises the current collector provided in the embodiment of the present invention.
[0096] Example 1
[0097] The specific surface area is 100m 2 / g of nickel foam was washed with acetone and water successively, and then placed in a dilute hydrochloric acid solution with a mass concentration of 1 mol / L to react for 1 hour. After the reaction was completed, it was washed with deionized water for several times to obtain clean nickel foam;
[0098] The clean nickel foam is placed in an oxygen environment at 120°C for oxidation treatment for 1 hour to form a uniform and dense nickel oxide layer on the surface of the nickel foam;
[0099] Weigh 0.1 mol of potassium ferrocyanide and dissolve it in 200 ml of water. Use dilute sulfuric acid to adjust the pH value of the solution to 3.5 to obtain a potassium ferrocyanide acid solution with a potassium ferrocyanide molar concentration of 0.5 mol / L. Seal it for later use.
[0100] 10 g of nickel oxide foam was placed in a sealed container containing an acid solution of ferrocyanide and allowed to stand for 1 hour to obtain nickel foam loaded with nickel ferrocyanide;
[0101] First calcination: Place the nickel foam loaded with nickel ferrocyanide in a tube furnace and calcine for 6 hours at 700°C in an environment with an argon and hydrogen volume ratio of 1:1 to obtain a nickel-iron-carbon precursor;
[0102] Second calcination: introduce carbon dioxide into the tube furnace and exhaust the argon and hydrogen therein, maintain the temperature at 700° C. for calcination for 30 min, and anneal for 60 min to obtain an iron-nickel porous carbon precursor;
[0103] 1 g of sodium hypophosphite was weighed and placed in the middle section of the quartz tube of the tubular furnace, 8 g of iron-nickel porous carbon precursor was placed directly above the sodium hypophosphite, argon gas was introduced into the tubular furnace, the ambient temperature was raised to 200°C, and pre-calcined for 1 hour to allow the sodium hypophosphite to completely decompose into phosphine that filled the tubular furnace. The temperature was then raised to 400°C, calcined for 6 hours, and annealed for 1 hour to obtain a sodium ion negative electrode-free battery current collector with nickel foam as the matrix and a composite of iron phosphide and porous carbon formed on the surface of the nickel foam and the pore walls of the pores.
[0104] The mass ratio of iron phosphide to nickel foam matrix in the current collector was measured by weighing calculation method, and was about 50:100, and the mass ratio of porous carbon to nickel foam matrix was about 50:100.
[0105] The SEM image of the current collector of the sodium ion negative electrode-free battery is shown in FIG. Figure 1 and Figure 2 As shown in the figure, it can be seen that a complex is formed on the surface of the three-dimensional skeleton of the nickel foam.
[0106] Example 2
[0107] The specific surface area is 100m 2 / g of nickel foam was washed with acetone and water successively, and then placed in a dilute hydrochloric acid solution with a mass concentration of 1 mol / L to react for 1 hour. After the reaction was completed, it was washed with deionized water for several times to obtain clean nickel foam;
[0108] The clean nickel foam was placed in an oxygen environment at 100°C for 1.5 hours to form a uniform and dense nickel oxide layer on the surface of the nickel foam.
[0109] Weigh 0.14 mol of potassium ferrocyanide and dissolve it in 200 ml of water. Use dilute sulfuric acid to adjust the pH value of the solution to 4 to obtain a potassium ferrocyanide acid solution with a potassium ferrocyanide molar concentration of 0.7 mol / L. Seal it for later use.
[0110] 10 g of nickel oxide foam was placed in a sealed container containing an acid solution of ferrocyanide and allowed to stand for 1 hour to obtain nickel foam loaded with nickel ferrocyanide;
[0111] First calcination: Place the nickel foam loaded with nickel ferrocyanide in a tube furnace and calcine for 5 hours at 800°C in an environment with an argon and hydrogen volume ratio of 1:1 to obtain a nickel-iron-carbon precursor;
[0112] Second calcination: introduce carbon dioxide into the tube furnace and exhaust the argon and hydrogen therein, maintain the temperature at 800° C. for calcination for 10 min, and anneal for 50 min to obtain an iron-nickel porous carbon precursor;
[0113] Weigh 0.8g of sodium hypophosphite and put it into the middle section of the quartz tube of the tubular furnace, place 9g of iron-nickel porous carbon precursor just above the sodium hypophosphite, introduce argon into the tubular furnace, raise the ambient temperature to 180°C, pre-calcine for 2.5h to completely decompose the sodium hypophosphite into phosphine that fills the tubular furnace, then raise the temperature to 350°C, calcine for 7h, and anneal for 1h to obtain a sodium ion negative electrode-free battery current collector with nickel foam as the matrix and a composite of iron phosphide and porous carbon formed on the surface of the nickel foam and the pore walls of the pores.
[0114] The mass ratio of iron phosphide to nickel foam matrix in the current collector was measured by weighing and calculating, and was about 40:100, and the mass ratio of porous carbon to nickel foam matrix was about 60:100.
[0115] Example 3
[0116] The specific surface area is 100m 2 / g of nickel foam was washed with acetone and water successively, and then placed in a dilute hydrochloric acid solution with a mass concentration of 1 mol / L to react for 1 hour. After the reaction was completed, it was washed with deionized water for several times to obtain clean nickel foam;
[0117] The clean nickel foam was placed in an oxygen environment at 140°C for 0.5 h to form a uniform and dense nickel oxide layer on the surface of the nickel foam.
[0118] Weigh 0.02 mol of potassium ferrocyanide and dissolve it in 200 ml of water. Use dilute sulfuric acid to adjust the pH value of the solution to 3 to obtain a potassium ferrocyanide acid solution with a potassium ferrocyanide molar concentration of 0.1 mol / L. Seal it for later use.
[0119] 10 g of nickel oxide foam was placed in a sealed container containing an acid solution of ferrocyanide and allowed to stand for 1 hour to obtain nickel foam loaded with nickel ferrocyanide;
[0120] First calcination: Place the nickel foam loaded with nickel ferrocyanide in a tube furnace and calcine for 7 hours at 600°C in an environment with an argon and hydrogen volume ratio of 1:1 to obtain a nickel-iron-carbon precursor;
[0121] Second calcination: introduce carbon dioxide into the tube furnace and exhaust the argon and hydrogen therein, maintain the temperature at 600° C. for calcination for 40 min, and anneal for 70 min to obtain an iron-nickel porous carbon precursor;
[0122] Weigh 1g of sodium hypophosphite and put it into the middle section of the quartz tube of the tubular furnace, place 9g of iron-nickel porous carbon precursor just above the sodium hypophosphite, introduce argon into the tubular furnace, raise the ambient temperature to 220°C, pre-calcine for 1.5h to allow the sodium hypophosphite to completely decompose into phosphine that fills the tubular furnace, then raise the temperature to 450°C, calcine for 5h, and anneal for 1h to obtain a sodium ion negative electrode-free battery current collector with nickel foam as the matrix and a composite of iron phosphide and porous carbon formed on the surface of the nickel foam and the pore walls of the pores.
[0123] The mass ratio of iron phosphide to nickel foam matrix in the current collector was measured by weighing calculation method, and was about 45:100, and the mass ratio of porous carbon to nickel foam matrix was about 55:100.
[0124] Comparative Example 1
[0125] This comparative example is basically the same as Example 1, except that there is no second calcination step.
[0126] Comparative Example 2
[0127] This comparative example provides a method for preparing a current collector in which the coating component on the surface of nickel foam and the pore walls is only porous carbon, specifically:
[0128] The cleaned nickel foam after the first step of the treatment in Example 1 is placed in a tube furnace, methane gas is introduced into the tube furnace, the temperature in the tube furnace is increased to 800° C., and calcined for 0.5 h to deposit a carbon layer on the surface and in the pores of the nickel foam to obtain nickel foam loaded carbon;
[0129] Carbon dioxide was introduced into the tubular furnace and the methane therein was evacuated. The temperature was maintained at 700° C. for calcination for 30 min. The porous carbon supported by nickel foam was annealed for 60 min. The ratio of porous carbon to nickel foam in the porous carbon supported by nickel foam was 50:100.
[0130] Comparative Example 3
[0131] This comparative example is basically the same as Example 2, except that the first calcination temperature is 900°C.
[0132] Comparative Example 4
[0133] This comparative example is basically the same as Example 3, except that the first calcination temperature is 500°C.
[0134] Comparative Example 5
[0135] This comparative example is basically the same as Example 2, except that the second calcination temperature is 900°C.
[0136] Comparative Example 6
[0137] This comparative example is basically the same as Example 3, except that the second calcination temperature is 500°C.
[0138] Experimental example
[0139] The products obtained in the above-mentioned embodiments and comparative examples are used as current collectors for negative electrode-free batteries to assemble batteries. The specific assembly method is as follows:
[0140] Sodium ferric phosphate pyrophosphate was selected as the positive electrode material, and a positive electrode sheet with a surface density of 25 g / cm2 was prepared using a coating formula (N-methylpyrrolidone was used as the solvent, the solid material composition was sodium ferrous sulfate, PVDF (polyvinylidene chloride), SP (carbon black) and PVP (polyvinyl pyrrolidone), and the mass ratio of sodium ferrous sulfate, PVDF, SP and PVP was 100:7:10:3);
[0141] The products prepared in the above-mentioned embodiments and comparative examples serve as negative electrodes;
[0142] The diaphragm is a commercial polypropylene dry-process diaphragm with a thickness of 20 microns;
[0143] Diethylene glycol dimethyl ether was selected as the solvent, NaTFSI as the sodium salt and aniline (final concentration was 1 M) as the additive to prepare an organic solvent electrolyte of 1 M sodium salt;
[0144] Finally, a 5Ah soft pack battery was made.
[0145] Each embodiment and comparative example was tested for 0.1C / 0.1C charge / discharge capacity, first coulomb efficiency, capacity retention rate at 5C rate, capacity retention rate after 100 cycles of 0.1C / 0.1C charge / discharge, gas production after 100 cycles of 0.1C / 0.1C charge / discharge, and capacity retention rate after 300 cycles of 0.5C / 1C high temperature (45°C). The test results are recorded in Table 1.
[0146] Table 1 Electrochemical properties of the batteries prepared in the examples and comparative examples
[0147]
[0148] It can be seen from Table 1 that the current collectors prepared in various embodiments of the present invention have better performance after being assembled into batteries, and their cyclability is relatively high, which can indicate that the current collectors prepared in various embodiments of the present invention have almost no sodium dendrite growth after 300 cycles.
[0149] Comparing Comparative Example 1 with Example 1, Comparative Example 1 does not have a second calcination step, so the carbon in its coating has no porous structure. The capacity retention rate and other properties of Comparative Example 1 are significantly worse, indicating that porous carbon can provide the current collector with more abundant sodium deposition sites and better inhibit the growth of sodium dendrites.
[0150] Comparing Comparative Example 2 with Example 1, the current collector prepared in Comparative Example 2 does not contain iron phosphide. The test results show that the capacity retention rate of Comparative Example 2 is significantly worse, indicating that the nickel phosphide in the coating can significantly improve the conductivity of the coating, so that the current collector can better inhibit the growth of sodium dendrites.
[0151] Comparing Comparative Example 3 with Example 2, the cyclability of Comparative Example 3 is significantly worse, indicating that the first calcination temperature is too high, affecting the toughness of the carbonized material, resulting in poor cyclability; comparing Comparative Example 4 with Example 3, the capacity of Comparative Example 4 is significantly worse, indicating that the first calcination temperature is too low, carbonization is incomplete, resulting in poor capacity. This shows that the temperature of the first calcination should be within the range of 600-800°C. If the temperature is too high or too low, a current collector with good performance cannot be obtained.
[0152] Comparing Comparative Example 5 with Example 2, the cyclability of Comparative Example 5 is significantly worse, indicating that the second calcination temperature is too high, which may cause excessive consumption of carbon particles, resulting in a reduction in active sites, resulting in poor cyclability; Comparative Example 6 with Example 3, the capacity of Comparative Example 6 is significantly worse, indicating that the second calcination temperature is too low, which may result in less pore formation of carbon particles, resulting in poor sodium embedding ability of active sites, resulting in poor capacity. This shows that the temperature of the second calcination should be in the range of 600~800℃. If the temperature is too high or too low, a current collector with good performance cannot be obtained.
[0153] The sodium ion negative electrode-free battery current collector provided by the embodiment of the present invention has an excellent three-dimensional structure, and the combination of the nickel foam and the porous carbon loaded on the surface and the pore wall of the pore structure can give the current collector an ultra-high specific surface area; the porous carbon has a rich pore structure, which can provide abundant sites for the deposition of sodium ions; and the iron phosphide can increase the conductivity of the composite. Therefore, the sodium ion negative electrode-free battery current collector provided by the embodiment of the present invention has abundant sodium ion deposition sites and excellent conductivity, and has the effect of inhibiting the growth of sodium dendrites.
[0154] The embodiment of the present invention provides a method for preparing a sodium ion negative electrode-free battery current collector, which can produce a sodium ion negative electrode-free battery current collector with excellent electrochemical properties provided by the embodiment of the present invention.
[0155] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a sodium ion negative electrode-free battery current collector, characterized in that: The sodium ion negative electrode-free battery current collector comprises a foam nickel matrix and a composite supported on the surface of the foam nickel matrix and the pore walls of the pores; The components of the composite include iron phosphide and porous carbon; The mass ratio of the porous carbon to the iron phosphide is 1-1.5:1; The mass ratio of the composite to the nickel foam matrix is 4-5:5; The preparation method of the sodium ion negative electrode-free battery current collector comprises: Oxidizing the nickel foam to form a nickel oxide layer on the surface of the nickel foam to obtain an oxidized nickel foam; Mixing the oxidized nickel foam and an acid solution of ferrocyanide to react, so that the nickel oxide on the surface of the oxidized nickel foam reacts with the ferrocyanide to generate nickel ferrocyanide, thereby obtaining nickel foam-loaded nickel ferrocyanide; The nickel foam loaded nickel ferrocyanide is placed in an environment of 600-800° C. and calcined to convert the nitrogen element in the cyanide into nitrogen gas overflow, the carbon in the cyanide into elemental carbon particles, and the iron element into elemental iron, to obtain a nickel-iron-carbon precursor; The nickel-iron-carbon precursor is calcined at 600-800° C. for 10-40 min in a carbon dioxide atmosphere, so that the carbon dioxide partially reacts with the elemental carbon particles to generate carbon monoxide, and a porous structure is formed on the carbon particles, thereby converting the elemental carbon particles into porous carbon, thereby obtaining an iron-nickel porous carbon precursor; The iron-nickel porous carbon precursor is fully reacted with phosphine gas at 350-450° C. in a closed environment, so that iron and phosphorus react to form iron phosphide, thereby obtaining a sodium ion negative electrode-free battery current collector.
2. The preparation method according to claim 1, characterized in that: Before the nickel foam is oxidized, the surface of the nickel foam is treated to remove the original uneven oxide layer on the surface of the nickel foam; The method of removing the original uneven oxide layer on the surface of the nickel foam includes: washing the nickel foam with acetone and water in turn, and then placing it in an acid solution for reaction.
3. The preparation method according to claim 1, characterized in that: It includes at least one of the following technical features (1) and (2): (1) The acid solution is selected from at least one of dilute sulfuric acid, dilute hydrochloric acid, citric acid and tartaric acid; (2) The molar concentration of the acid solution is 0.5-1 mol / L, and the reaction time is 1-6 h.
4. The preparation method according to claim 1, characterized in that: The invention comprises at least one of the following features (1) to (11); (1) The pH of the acid solution of ferrocyanide is 2 to 5; (2) The ferrocyanide is at least one selected from potassium ferrocyanide, potassium ferrocyanide and sodium ferrocyanide; (3) The mixed reaction of the nickel oxide foam and the acid solution of ferrocyanide is carried out in a sealed container; (4) The molar concentration of ferrocyanide in the acid solution of ferrocyanide is 0.1 to 0.7 mol / L; (5) The mass ratio of the acid solution of ferrocyanide to the nickel oxide foam is 20-100:5; (6) The acid solution of ferrocyanide is a mixture of ferrocyanide and dilute acid, and the dilute acid is dilute sulfuric acid or dilute hydrochloric acid; (7) The method of oxidizing the nickel foam includes: placing the nickel foam in an oxygen environment at 100-140° C. for oxidation treatment for 0.5-1.5 hours; (8) mixing the nickel oxide foam and the acid solution of ferrocyanide for a reaction time of 0.5 to 2 hours; (9) calcining the nickel foam loaded with nickel ferrocyanide is carried out in an argon atmosphere or a mixed atmosphere of argon and hydrogen; (10) When the nickel foam loaded with nickel ferrocyanide is calcined, the calcination time is 5 to 7 hours; (11) After calcining the nickel-iron-carbon precursor in a carbon dioxide atmosphere, annealing is further performed for 50 to 70 minutes.
5. The preparation method according to claim 1, characterized in that: The method of fully reacting the iron-nickel porous carbon precursor with phosphine gas at 350-450° C. in a closed environment includes: In a closed environment with an inert atmosphere, sodium hypophosphite is decomposed into phosphine gas which fills the closed environment. The temperature of the closed environment is controlled to be 350-450° C. and the reaction is carried out for 5-7 hours.
6. The preparation method according to claim 5, characterized in that: The mass ratio of the amount of sodium hypophosphite to the nickel foam is 1-0.8:
5.
7. The preparation method according to claim 5, characterized in that: It also includes at least one of the following features (1) to (3): (1) controlling the temperature of the sealed environment to be 350-450° C., reacting for 5-7 hours, and then annealing for 50-70 minutes; (2) The inert atmosphere is an argon atmosphere; (3) The method of decomposing sodium hypophosphite into phosphine includes: placing the sodium hypophosphite in a closed environment with an inert atmosphere, raising the ambient temperature to 180-220°C, and maintaining it for 1.5-2.5 hours to allow the sodium hypophosphite to completely decompose.
Citation Information
Patent Citations
Preparation method of self-supporting three-dimensional porous carbon negative electrode material
CN110061236A
Iron phosphide modified porous carbon sphere composite material as well as preparation and application thereof
CN116715217A